Integrated vocational training of specialists under the EРP «Vocational Education (Crafts and Food Technologies)» - Burak, Valentyna; Sorokina, Alyona; Voloshyn, Alexander (ScienceRise: Pedagogical Education, 2026)
The article substantiates the features of vocational training of specialists through the integration of knowledge, skills, abilities, competencies in craft production and food technologies and pedagogy, psychology and methodology. Leading trends are associated with the introduction of innovative technologies to improve the quality, safety and competitiveness of products in the domestic and foreign markets; innovative processing of plant raw materials to create functional food products; the introduction of intelligent quality control systems, digital product labeling, online sales through electronic platforms; the implementation of bioengineering and functional food industry technologies. The analysis of psychological and pedagogical literature indicates the systematic use of digital technologies; modernization of educational programs for vocational training; differentiated and high-quality training of all levels of specialists; use of project learning technology and opportunities for advanced education. The essence of integrated vocational training of specialists under the EPP "Vocational Education (Craft Production and Food Technologies)" is analyzed. Its uniqueness is proven, which is manifested in the training of specialists for the implementation of educational activities in the vocational training of technical specialists, qualified workers and employees of enterprises, institutions and organizations in the fields of education, agricultural production, product processing and food technologies, the formation of readiness for self-education and professional self-improvement throughout life. Recommendations are proposed for the implementation of the specified EPP in a higher education institution, which include a number of reasoned provisions: ensuring the conceptual and methodological compliance of EPP with modern educational standards and labor market needs, implementing a practice-oriented mechanism for vocational training of education seekers, integrating digital technologies into the educational process of vocational training of specialists, developing the pedagogical component of training for teachers of vocational education, forming entrepreneurial and innovative competence of future specialists, implementing a system for ensuring the quality of education, developing international cooperation and academic mobility